Below‐ground processes control the success of an invasive seaweed. (10th April 2018) - Gribben, Paul E.; Thomas, Torsten; Pusceddu, Antonio; Bonechi, Lisa; Bianchelli, Silvia; Buschi, Emanuela; Nielsen, Shaun; Ravaglioli, Chiara; Bulleri, Fabio
Abstract: Whilst the successful establishment and spread of invasive species can be determined by above‐ground processes, results are often equivocal. Emergent research, mostly from terrestrial ecosystems, demonstrates that below‐ground processes (nutrient cycling, chemical properties) under microbial control can mediate interactions between native and invasive plants. Because microbes can control similar sediment properties in marine ecosystem that influence plant fitness, we argue that below‐ground properties should also exert strong control interactions between native and invasive marine macrophytes. We coupled surveys of microbial communities and chemistry of sediments collected from an invasive alga ( Caulerpa cylindracea ), a native competitor (the seagrass Posidonia oceanica ) and unvegetated sediments with a large field experiment, in which we manipulated the presence/absence of the canopies of both species to determine the effects of above‐ and below‐ground processes on the success of C. cylindracea . Posidonia oceanica and C. cylindracea sediments have microbial communities and predicted metabolic process that reflect aerobic and anaerobic conditions, respectively. Moreover, the nutritional quantity of organic matter was higher, but quality lower in C. cylindracea sediments compared to the two native habitats. The growth of C. cylindracea fragments was equally low in the presence or absence of a P. oceanica canopy, whereas the growth of C. cylindracea was higher in the canopy removed vs. present treatment, possibly because, in the absence of a C. cylindracea canopy, fragments are released from intraspecific competition for resources. Synthesis . Sediment/soil processes are increasingly recognized as important drivers of the success and hence impacts of invasive plants. We extended this theory to marine ecosystems and suggest biotic resistance to invasion may not always be attributable to intact canopies, but may also result from indirect effects of native macrophytes on sediment quality and microbial processes. This information may, in part, resolve why above‐ground interactions do not always explain invasive plant success and thus can be used to develop better informed management strategies. Abstract : Sediment/soil processes are increasingly recognized as important drivers of the success and hence impacts of invasive plants. We extended this theory to marine ecosystems and suggest biotic resistance to invasion may not always be attributable to intact canopies, but may also result from indirect effects of native macrophytes on sediment quality and microbial processes. This information may, in part, resolve why above‐ground interactions do not always explain invasive plant success and thus can be used to develop better informed management strategies.